Provisional Climatic Regions of Peninsular Malaysia - Bishop, I. D. (1984)
Using a micro-computer based geographic information system for Peninsular Malaysia and a simple method of cluster analysis, a provisional statistical classification of climatic zones was produced. Eight separate zones were identified and were described in terms such as 'dry sunny lowlands' and 'wet cloudy uplands'. For a number of reasons, including limitations in the data base, these zones are described as provisional. The procedures involved however have great potential for contributing to better environmental and landuse plannitng.